Progressive taxation and (in)stability in an exogenous growth model with Epstein-Zin recursive preferences - Aleksandar Vasilev (Economics and Econometrics Research Institute (EERI), 2019)
We show that in an exogenous growth model with Epstein-Zin (1989, 1991) recursive preferences calibrated to Bulgarian data under the progressive taxation regime (1993- 2007), the economy exhibits equilibrium indeterminacy. These results are in line with the findings in Benhabib and Farmer (1994, 1996) and Farmer (1999). Also, the findings in this paper are in contrast to Guo and Lansing (1988) who argue that progressive taxation works as an automatic stabilizer. In contrast, under the flat tax regime (2008- 16), the same economy calibrated to Bulgarian data now displays saddle-path stability. The decrease in the average effective tax rate addresses the indeterminacy issue and eliminates the 'sink' dynamics.
Keywords: H22; J46; D51; D91; O41; 330; Progressive taxation; Epstein-Zin preferences; Equilibrium (In)determinacy; Bulgaria